2017
DOI: 10.1111/jvim.14838
|View full text |Cite
|
Sign up to set email alerts
|

Antihistone Autoantibodies in Dobermans With Hepatitis

Abstract: BackgroundImmune system involvement is suggested as an underlying cause for Doberman hepatitis (DH) based on female predisposition, lymphocyte infiltration, abnormal hepatocyte expression of major histocompatibility complex class II antigens, and homozygosity for dog leukocyte antigen DRB1*00601.ObjectiveTo measure serum antinuclear antibodies (ANA) and serum antihistone antibodies (AHA) in Dobermans with hepatitis. To determine whether increased serum ANA or serum AHA could be used to support the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Recent studies have shown evidence that the development of chronic hepatitis in Dobermanns has an autoimmune component . High hepatic copper concentrations cause or contribute to progression of chronic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown evidence that the development of chronic hepatitis in Dobermanns has an autoimmune component . High hepatic copper concentrations cause or contribute to progression of chronic hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Specific criteria for the diagnosis of immune‐mediated hepatitis in dogs have not been developed. An immune basis in some dogs with idiopathic CH is suggested by several criteria (Table ) which include the presence of lymphocytic infiltrates in the liver, abnormal expression of major histocompatibility complex class II proteins, positive serum autoantibodies, familial history of liver disease, association with other immune‐mediated disorders, female predisposition, and favorable response to immunosuppression . A presumptive clinical diagnosis of immune‐mediated CH in the dog requires elimination of other etiologies and a favorable response to immunosuppressive treatment.…”
Section: Etiologymentioning
confidence: 99%
“…Details and evidence for breed, sex, and age predispositions are summarized in Supporting Information Table S1. There is strong evidence in ≥2 studies for an increased prevalence of CH in BT, Doberman Pinschers, LR, Dalmatians, American and English Cocker Spaniels, English Springer Spaniels, and West Highland White Terriers in several countries. In addition, in Sweden the Scottish Terrier, and in the United Kingdom the Cairn Terrier, Great Dane, Samoyed, Yorkshire Terrier, and Jack Russell Terrier are predisposed .…”
Section: Signalment and Clinical Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 More recently, autoantibodies against liver proteins were found in sera of Doberman pinschers with CH before the onset of clinical signs. 32 Using an indirect immunofluorescence assay on cryostat sections of mouse liver small numbers of Doberman's with CH had evidence of antinuclear antibodies, 33 and IgG autoantibodies against histones. 34 However, the question that remains from all these studies is whether these autoantibodies are the primary cause of the disease, or a secondary phenomenon.…”
Section: Etiologymentioning
confidence: 99%